Outcomes After Percutaneous Coronary Intervention or Bypass Surgery in Patients With Unprotected Left Main Disease - Cavalcante, Rafael; Sotomi, Yohei; Lee, Cheol W.; Ahn, Jung-Min; Farooq, Vasim; Tateishi, Hiroki; Tenekecioglu, Erhan; Zeng, Yaping; Suwannasom, Pannipa; Collet, Carlos; Albuquerque, Felipe N.; Onuma, Yoshinobu; et al. (Journal of the American College of Cardiology, 2016)
Currently available randomized data on the comparison between percutaneous coronary intervention (PCI) and coronary artery bypass graft (CABG) for the treatment of unprotected left main coronary disease (LMD) lacks statistical power due to low numbers of patients enrolled. This study assessed long-term outcomes of PCI and CABG for the treatment of LMD in specific subgroups according to disease anatomic complexity. We conducted a pooled analysis of individual patient-level data of the LMD patients included in the PRECOMBAT (Bypass Surgery Versus Angioplasty Using Sirolimus-Eluting Stent in Patients With Left Main Coronary Artery Disease) and SYNTAX (Synergy Between PCI With TAXUS and Cardiac Surgery) trials. Incidences of major adverse cardiac events were assessed at 5 years follow-up. Study population comprised 1,305 patients. The incidence of major adverse cardiac and cerebrovascular events at 5 years was 28.3% in the PCI group and 23.0% in the CABG group (hazard ratio [HR]: 1.23; 95% confidence interval [CI]: 1.01 to 1.55; p = 0.045). This difference is mainly driven by a higher rate of repeat revascularization associated with PCI (HR: 1.85; 95% CI: 1.38 to 2.47; p < 0.001). The 2 strategies showed similar rates of the safety composite endpoint of death, myocardial infarction, or stroke (p = 0.45). In patients with isolated LM or LM + 1-vessel disease, PCI was associated with a 60% reduction in all-cause mortality (HR: 0.40; 95% CI: 0.20 to 0.83; p = 0.029) and 67% reduction in cardiac mortality (HR: 0.33; 95% CI: 0.12 to 0.88; p = 0.025) when compared with CABG. In patients with unprotected LMD, CABG, and PCI result in similar rates of the safety composite endpoint of death, myocardial infarction, or stroke. In patients with isolated LM or LM + 1-vessel disease, PCI is associated with lower all-cause and cardiac mortality when compared to CABG.